2016
DOI: 10.3892/etm.2016.3401
|View full text |Cite
|
Sign up to set email alerts
|

Effects of survivin on FVADT chemotherapy for refractory multiple myeloma

Abstract: Abstract. The present study aimed to investigate the effects of survivin, an apoptosis inhibitor protein, on the efficacy of the fludarabine, vincristine, epirubicin, dexamethasone and thalidomide (FVADT) chemotherapy regime for the treatment of refractory multiple myeloma (MM). A total of 82 patients with MM were selected from the Hematology Inpatient Department at The Second Affiliated Hospital of Zhengzhou University (Zhengzhou, China). The initial treatment group consisted of 40 patients with MM, who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Besides, Yang et al. [21] represented that the positive expression rate of survivin was significantly increased in patients with multiple refractory myelomas (MRM), and the patients with high expression of survivin had increased drug resistance and harsher chemotherapeutic effects. Using siRNA- survivin drugs would completely reverse vincristine resistance, which suggested that the siRNA- survivin drug was the potentially proper treatment of vincristine-resistant MRM [22] .…”
Section: The Pharmacological Actions Of Sirna Drugs For Remodeling Tmementioning
confidence: 99%
“…Besides, Yang et al. [21] represented that the positive expression rate of survivin was significantly increased in patients with multiple refractory myelomas (MRM), and the patients with high expression of survivin had increased drug resistance and harsher chemotherapeutic effects. Using siRNA- survivin drugs would completely reverse vincristine resistance, which suggested that the siRNA- survivin drug was the potentially proper treatment of vincristine-resistant MRM [22] .…”
Section: The Pharmacological Actions Of Sirna Drugs For Remodeling Tmementioning
confidence: 99%
“…An assessment of the level of survivin may have significance in the prognosis of oncological treatment, e.g. multiple myeloma [7], adenoid cystic carcinoma of the lacrimal gland [8], ovarian cancer [9] and osteosarcoma [10]. Peroukides et al studied the protein expression of survivin in 69 cases of HCC and adjacent liver cirrhosis, and demonstrated increased protein levels and distinct sub cellular localization of survivin in HCC and liver cirrhosis [11].…”
Section: Discussionmentioning
confidence: 99%
“…Survivin has been reported to inhibit apoptosis and regulate mitosis as well as cytokinesis. Studies indicate that survivin expression correlates with proliferation and poor overall survival of patients, as well as treatment failure [181,182] . XIAP (inhibitor of apoptosis protein) expression appears elevated in many cancer cells often conferring resistance to chemotherapy-induced cell death [183] .…”
Section: Role Of Microenvironmentmentioning
confidence: 99%